(untitled) (مجلة المنصور, 2022)
Control of institutional operations are carried out by representatives of stakeholders to provide supervision of risk management and control risks of the organization and the emphasis on the adequacy of controls to avoid these risks, which leads to the direct contribution in the achievement of goals and increase the value of the organization, and perhaps is the question "of these actors that contribute to risk management based on rules of institutional control? "The answer to this question was the subject of this research to shed light on the concept of risk management and its relationship to the institutional control and identification of which can contribute to identifying, measuring and testing and evaluation of risk management. And to identify the extent of the commitment of both boards of directors and the internal auditor and external auditor and audit committees the requirements of corporate governance in risk management in the Arab Bank and Chkhies the negative and positive aspects of practical applications for risk management and submission of proposals that would increase the effectiveness of risk management in Aalpennek The results showed that there is a recognition great importance to these agencies for their role in risk management but differentiated one from the other and to promote this awareness is necessary to adhere to the principles and standards of the International Auditing and amending legislation related to the duties of these entities and the holding of training courses, continuing all management levels to familiarize them with the elements of corporate governance and effective role in risk management.